Clustered Regularly Interspaced Short Palindromic Repeats-Associated Protein System for Resistance Against Plant Viruses: Applications and Perspectives - Silva, Fredy D. A.; Fontes, Elizabeth P. B. (Frontiers in Plant Science, 2022)
Different genome editing approaches have been used to engineer resistance against plant viruses. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas; CRISPR/Cas) systems to create pinpoint genetic mutations have emerged as a powerful tool for molecular engineering of plant immunity and increasing resistance against plant viruses. This review presents (i) recent advances in engineering resistance against plant viruses by CRISPR/Cas and (ii) an overview of the potential host factors as targets for the CRISPR/Cas system-mediated broad-range resistance and immunity. Applications, challenges, and perspectives in enabling the CRISPR/Cas system for crop protection are also outlined.